Analysis of Tafsir Methods and Sources in the Book of Al-Bahr Al-Madid Fi Tafsir Al-Qur'an Al-Majid by Ibn 'Ajibah (Surat Al-A'la) - Ratih Rahmawati; Syarah Sofiah Arifin; Eni Zulaiha; Wildan Taufiq (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Interpretation as a human product is greatly influenced by the knowledge and orientation of the interpreter, which causes various interpretations of the verses of the Qur'an. A theologian will interpret the Qur'an according to his knowledge as a mutakallim, as will a Sufi. One of the books of Islamic heritage is Tafsir Al Bahr Al-Madid fi Tafris Al-Qur'an Al-Majid by Ibn A'jibah. This book is one of the books of interpretation that uses the Sufi Ishari approach to interpretation. That is, a style of interpretation based on hidden signs behind the words that contradict the apparent interpretation of the verses of the Qur'an. This article will analyze how Ibn Ajibah interpreted in Tafsir Al-Bahr Al Madid. The objective of the study in this research is to introduce the book Al-Bahrul Madid by Ibn A'jibah along with the specific methods and sources of its interpretation. The method applied in this research is qualitative using literature study. The data was then analyzed using a special method of interpreting the Quran. This tafsir is generally not widely available, and not many researchers have studied or critiqued it. It is rarely referenced compared to other, more well-known Sufi-style tafsirs.